2000
DOI: 10.1051/analusis:2000129
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of some metals in wine by means of capillary electrophoresis. Application to the differentiation of Ribeira Sacra Spanish red wines

Abstract: Abstract. The content of some metals (Na, K, Ca, Mg, Mn and Li) in a variety of red wines produced in different geographical zones of Galicia was determined in a single analysis by capillary electrophoresis. Data were processed using multivariate supervised and non-supervised chemometric techniques involving cluster analysis, principal component analysis (PCA), linear discriminant analysis (LDA), K nearest neighbours (KNN) and soft independent modelling of class analogy (SIMCA). The results obtained have allow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
26
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 18 publications
3
26
0
Order By: Relevance
“…These results present mean values for the three measurements performed for each sample. The results of the analyses are summarised in Tables 6-8. A high dispersion of the contents of the elements observed in wines was also described in the literature (Núñez et al 2000;Banović et al 2009;Şen & Tokatli 2014). Our results showed that the mineral compositions of wine and soils were interrelated.…”
Section: Resultssupporting
confidence: 68%
See 3 more Smart Citations
“…These results present mean values for the three measurements performed for each sample. The results of the analyses are summarised in Tables 6-8. A high dispersion of the contents of the elements observed in wines was also described in the literature (Núñez et al 2000;Banović et al 2009;Şen & Tokatli 2014). Our results showed that the mineral compositions of wine and soils were interrelated.…”
Section: Resultssupporting
confidence: 68%
“…Potassium is the main positive ion in wine (Boulton et al 1996). A number of factors affect the amount of potassium in wine, including the variety of grapes, soil and climatic conditions, time of harvest, the temperature of fermentation and storage, and the pH and the use of ion-exchange resins (Núñez et al 2000). Its concentration in wine ranges from 200 mg/l to 2000 mg/l (Margalit 1997).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For Romania d is 1.04. account: the biochemical characteristics of the must and wine, the sugar content and its acidity (Bunea, 2010;Joshi et al, 2014;Yuyuen et al, 2015;Brunel et al, 2016;Catania et al, 2016). The grape quality is directly influenced by the variety, the ecoclimatic conditions, soil (physic-chemical characteristics of the soil), the wine-making process, the wine transportation and storage, the level of the agro-technical works applied and zoning (Coombe, 1987;Fernandez 1988;Núñez et al, 2000;Marini et al, 2006;Voica et al, 2009;Rotaru et al, 2010;Bora et al, 2015a;Condurso et al, 2015).…”
Section: Climatic Datamentioning
confidence: 99%